Digital Gamification in Senior High School Language Learning: A Systematic Literature Review Based on PRISMA 2020 - Kamilatu Zahra; Mursidin (Penerbit Minhaj Pustaka, 2026)
Digital transformation and the pedagogical demands of Society 5.0 are accelerating the adoption of gamification in senior-high-school language classrooms, yet research on how such gamification is managed remains scattered and has not been synthesized systematically. This study synthesizes empirical evidence on the management of digital gamification-based language-learning media in senior high schools, covering planning, organizing and implementation, evaluation, managerial challenges, and platform mapping. A Systematic Literature Review following the PRISMA 2020 protocol was conducted, searching Scopus, Google Scholar, ERIC, and DOAJ for studies published between 2022 and 2026; fifteen empirical articles met the inclusion criteria and were analyzed through thematic synthesis. The results show that effective management hinges on aligning game mechanics with linguistic objectives rather than on technological sophistication alone. The dominant obstacles are infrastructural inequality, gaps in teachers' digital-pedagogical competence, and the limited validity of automated assessment. Kahoot! and Quizizz dominate current practice, but their use remains concentrated on receptive and grammar-related skills. The study proposes a cyclical framework for managing language gamification and underscores the need for further research on productive-skill applications within local contexts.